Working Group II: The Threat from Armed Conflict and Terrorism - Arlosoroff, S. (Threats to Global Water Security, 2009)
Both terrorism and armed conflict can be threats to water security, either directly or indirectly. Both forms of violence have used disruption or poisoning of water supplies as a weapon, and both may cause collateral damage to water supplies. The distinction between war and terrorism can be arguable. Special Operations forces may use some tactics similar to terrorists, with similar repercussions for water systems, but the main practical distinction is between formal military actions and more informal, smaller scale guerrilla-style activities that may be directed more at civilian personnel and designed to engender fear and panic as much as specific damage.